Can a person prepare to become a Christian? A Kierkegaardian response. Issue 2 (27th July 2016) - TORRANCE, ANDREW B.
Abstract: Is it possible to prepare oneself to become a Christian? For Kierkegaard, there is no straightforward answer to this question, especially since such a transition depends upon a divine activity that is outside the realm of human control. Despite the challenge that this question poses, Kierkegaard's writings do provide us with a way to respond, and this response will be the subject matter of this article. Following an analysis of his position, this article will conclude that, although Kierkegaard recognizes that there are precedent ways of existing that are more conducive to becoming a Christian, it is not helpful to describe them as preparatory.